Optimizing Islamic Education Learning Outcomes through the Two Stay Two Stray Method with Question Board - Yufi Mohammad Nasrullah; Hilda Ainissyifa; Syifa Nuril Asfiya; Nurul Fatonah; Fiqra Muhamad Nazib; Mohd Izwan Shahril (Jurnal al-Thullab, 2024)
This study is grounded in the need to improve students’ learning outcomes in Islamic Religious Education (IRE), which are often hindered by monotonous teaching methods and limited student engagement. The objective of this research is to examine the effectiveness of the Two Stay Two Stray (TSTS) method supported by question board media in enhancing students’ understanding and achievement. This study employed a quantitative approach using a Classroom Action Research (CAR) design, involving 25 twelfth-grade students. Data were collected through pretest and posttest assessments, classroom observations, and student questionnaires. The findings reveal a significant improvement in learning outcomes, as indicated by the increase in mean scores from 73.8 in the pretest to 90.2 in the posttest. Statistical analysis shows that the t-count (4.30) exceeds the t-table (2.06), confirming a significant difference after the intervention. Furthermore, the implementation of TSTS encourages active participation, collaboration, and critical thinking, while the question board media supports students in understanding abstract religious concepts. This study contributes to the development of innovative and interactive learning strategies in Islamic education by integrating cooperative learning models with visual media to optimize student engagement and comprehension.